2014
DOI: 10.4162/nrp.2014.8.1.94
|View full text |Cite
|
Sign up to set email alerts
|

Early dropout predictive factors in obesity treatment

Abstract: Diet attrition and failure of long term treatment are very frequent in obese patients. This study aimed to identify pre-treatment variables determining dropout and to customise the characteristics of those most likely to abandon the program before treatment, thus making it possible to modify the therapy to increase compliance. A total of 146 outpatients were consecutively enrolled; 73 patients followed a prescriptive diet while 73 followed a novel brief group Cognitive Behavioural Treatment (CBT) in addition t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
50
1
3

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(57 citation statements)
references
References 40 publications
3
50
1
3
Order By: Relevance
“…Where a relationship does exist it appears that females may be more likely to drop out than males 2 , although a more recent study has shown that males are more likely to drop out than females 23 . The 2011 systematic review found roughly equal (but small n=4-5) numbers of papers supporting a relationship between high or low initial weight and attrition compared with 18 reporting no relationship more recent papers continue to differ with some supporting the relationship between higher initial weight 18,20 and attrition and some lower initial weight 15 (although no relationship is still the most frequent 9,17,19 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Where a relationship does exist it appears that females may be more likely to drop out than males 2 , although a more recent study has shown that males are more likely to drop out than females 23 . The 2011 systematic review found roughly equal (but small n=4-5) numbers of papers supporting a relationship between high or low initial weight and attrition compared with 18 reporting no relationship more recent papers continue to differ with some supporting the relationship between higher initial weight 18,20 and attrition and some lower initial weight 15 (although no relationship is still the most frequent 9,17,19 ).…”
Section: Discussionmentioning
confidence: 99%
“…The consideration that analyses investigating attrition are generally post hoc and unplanned also makes the relationship between attrition and gender and attrition and initial weight or BMI unclear as the majority of studies show no relationship 2,15,19 . Where a relationship does exist it appears that females may be more likely to drop out than males 2 , although a more recent study has shown that males are more likely to drop out than females 23 .…”
Section: Discussionmentioning
confidence: 99%
“…la cirugía; es decir, cuando debe comenzar el tratamiento nutricional. Para el análisis se utilizó como punto de corte 10% 17,18 y se definieron dos categorías: <10% y ≥10%.…”
Section: Resultsunclassified
“…Asumiendo un nivel de confianza del 95% (IC95%) y una potencia del 80%, se requerían como mínimo 288 participantes (144 participantes en cada grupo de acuerdo a exposición) para detectar una diferencia de 16% en las tasas de abandono, es decir, 46% 17 de abandono en aquellos que pierden menos del 10% de su peso, comparados con 30% 18 de abandono en aquellos que pierden más del 10%. Dos variables resultado fueron evaluadas: los criterios de inclusión para la cirugía bariátrica, definida según las guías americanas y europeas 6,7 , es decir, aquel paciente que tiene un IMC≥40kg/m 2 o ≥35kg/m 2 con comorbilidades como hipertensión y diabetes; y el abandono del tratamiento nutricional, entendido como la consulta y seguimiento llevado a cabo exclusivamente por la nutricionista, profesional que forma parte del equipo multidisciplinario según indicaciones internacionales 6,7,9 .…”
Section: Materials Y Métodosunclassified
See 1 more Smart Citation